Cobalt and manganese carboxylates for metal oxide thin film deposition by applying the atmospheric pressure combustion chemical vapour deposition process. Issue 28 (25th April 2018) - Kretzschmar, B. S. M.; Assim, K.; Preuß, A.; Heft, A.; Korb, M.; Pügner, M.; Lampke, T.; Grünler, B.; Lang, H.
Abstract : Complexes [M(O2 CCH2 OC2 H4 OMe)2 ] (M = Co, Mn) were synthesized characterised regarding their thermal behaviour. They were used as precursors for deposition of rough Co3 O4 and smooth Mn2 O3 /Mn3 O4 thin films via the CCVD process. Abstract : Coordination complexes [M(O2 CCH2 OC2 H4 OMe)2 ] (M = Co, 4 ; M = Mn, 5 ) are accessible by the anion exchange reaction between the corresponding metal acetates [M(OAc)2 (H2 O)4 ] (M = Co, 1 ; M = Mn, 2 ) and the carboxylic acid HO2 CCH2 OC2 H4 OMe (3 ). IR spectroscopy confirms the chelating or μ-bridging binding mode of the carboxylato ligands to M(ii ). The molecular structure of5 in the solid state confirms a distorted octahedral arrangement at Mn(ii ), setup by the two carboxylato ligands including their α-ether oxygen atoms, resulting in an overall two-dimensional coordination network. The thermal decomposition behavior of4 and5 was studied by TG-MS, revealing that decarboxylation occurs initially giving [M(CH2 OC2 H4 OMe)2 ], which further decomposes by M–C, C–O and C–C bond cleavages. Complexes4 and5 were used as CCVD (combustion chemical vapour deposition) precursors for the deposition of Co3 O4, crystalline Mn3 O4 and amorphous Mn2 O3 thin films on silicon and glass substrates. The deposition experiments were carried out using three different precursor solutions (0.4, 0.6 and 0.8 M) at 400 °C. Depending on the precursor concentration, particulated layers were obtained as evidenced by SEM. The layer thicknesses range from 32 to 170 nm. The rms roughness of the respective films was determined by AFM, displaying that the higher the precursor concentration, the rougher the Co3 O4 surface is (17.4–43.8 nm), while the manganese oxide films are almost similar (6.2–9.8 nm).